30 Past, present and future practice of surgical versus trans-catheter aortic valve replacement: a northern ireland perspective. (5th October 2017) - Toh, T; Hamid, U; Gregg, A; Nzewi, O; Austin, C; Owens, C; Manorharan, G; Spence, M; Jeganathan, R
Abstract : Introduction: Trans-catheter aortic valve implantation is now a Class 1 recommendation for high-risk patients alongside surgical aortic valve replacements and a Class 2 a recommendation for intermediate risk patients (AHA 2017 guidelines). The purpose of this study was to evaluate the change in clinical practice of surgical aortic valve replacement (SAVR) since the introduction of trans-catheter aortic valve implantation (TAVI) in Northern Ireland. Methods: A retrospective analysis was conducted on data collected from all patients who underwent SAVR and TAVI between 2008 and 2015. Patients who underwent emergency or salvage surgery, including those who underwent surgery for infective endocarditis were excluded from the analysis. TAVI and SAVR patients were compared for preoperative risk profile and short-term outcomes including in-hospital mortality and postoperative length of stay. Results: In total, 2152 SAVR and 517 TAVI procedures were performed during that period. Patients undergoing SAVR were younger than those undergoing TAVI (mean age 67.7 ±12.2 vs. 81.8±6.6 years) and had a lower preoperative logistic European System for Cardiac Operative Risk Evaluation (EuroSCORE) risk profile with a mean EuroSCORE of 8.2% ±8.9% vs. 18.6% ±11.8% (Table 1). The number of SAVR procedures increased from 207 in 2008 to 338 in 2015, while the number of TAVI increased from 21 in 2008 to 100 in 2015 (Figure 1). A reduction in SAVR was seen in octogenarian patients corresponding to increase in TAVI in the same age group (Figure 2). A reduction in concomitant SAVR was also seen from 2013 onwards, in line with increasing number of TAVIs with previous PCI (Figure 3). Postoperative length of stay also decreased in both groups from 13.7 to 12 days after SAVR and from 10.7 to 4.4 days after TAVI. In-hospital mortality decreased in both groups between 2008 and 2015, from 2.9% to 0.3% with SAVR and from 4.8% to 2.0% with TAVI (Figure 4). Conclusion: The findings demonstrate that both TAVI and SAVR practice has increased, paralleled with improved hospital outcomes. The latter is likely the result of good patient selection due to a robust MDT process. We estimate an increase in the utilisation of TAVI in the coming future as a result of the increasingly ageing population as witnessed over the last 3 years.